Think, for prevention! - Blas Ramírez, Lili María (2020)
This article has an objective to develop the capacity of critical thinking in dealing with cyberbullying. It addresses a population composed of high school students (2nd grade) from a private school, taking into account the following case studies dimensions: analysis of information, inferences and implications, alternatives of solutions and position of argument. Through the  application called “Critical thinking test” relevant information for the study can be collected. Furthermore, the intervention program involves the participation of affected students, aggressors and observers as well as parents, teachers and educational agents.